Revealing the Effect of Bonus Compensation, Political Costs, and Opportunistic Behavior on Earnings Management Practices in the Indonesian Insurance Industry - Nugroho, Tatas Ridho; Setiono, Hari; Ilmiddaviq, Muhammad Bahril (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the effect of compensation bonuses, political costs, and opportunistic behavior on earnings management in the Indonesian insurance sector for the period 2019-2023, which was chosen due to increased regulatory pressure and economic challenges due to the COVID-19 pandemic. Using a quantitative approach, this study analyzes secondary data from the financial statements of insurance companies listed on the Indonesia Stock Exchange using multiple regression methods. The results show that political costs are significantly positively related to earnings management, supporting Positive Accounting Theory, while bonus compensation is significantly negatively related, in line with Agency Theory, which asserts that performance-based incentives can reduce earnings manipulation. Opportunistic behavior has no significant effect, indicating the limitations of the proxy in the context of the insurance industry. This research enriches the literature and offers practical insights for regulators and policy makers.